Accumulation of Stinging Nettle Bioactive Compounds as a Response to Controlled Drought Stress - Mia Dujmović; Nevena Opačić; Sanja Radman; Sanja Fabek Uher; Sandra Voća; Jana Šic Žlabur (Agriculture, 2023)
As the impact of global warming intensifies drought effects, plants need to adapt to drought and other climate change-induced stresses through various defense mechanisms. One of them is the increased synthesis of bioactive compounds (BCs), which helps plants overcome adverse environmental conditions. This effect can be used in sustainable controlled cultivation as a tool for the nutritional improvement of crops, so this study focused on growing stinging nettle (Urtica dioica L.) for human consumption in a controlled environment. Since nettle can be consumed as a green leafy vegetable due to its nutritional value, the aim of this study was to determine the content of BCs (ascorbic acid, phenolic compounds, and pigments) and antioxidant capacity of nettle leaves grown under different drought stress conditions in an ebb and flow hydroponic system. During the experiment, plants were treated with a nutrient solution adjusted for nettle cultivation for 1 hour and then exposed to three different drought intervals: 24, 48, and 96 h. During the 48 h drought interval, the plants accumulated the highest amounts of total phenolic content and total non-flavonoid content (400.21 and 237.33 mg GAE/100 g, respectively), and during the 96 h drought interval, the nettle accumulated the highest amount of ascorbic acid (96.80 mg/100 g fw). The highest antioxidant capacity was recorded during the 24 and 48 h treatments (2435.07 and 2444.83 µmol/TE, respectively) according to the ABTS and during the 48 h treatment (3773.49 µmol/TE) according to the FRAP assay. The obtained results show that different drought stress durations caused by the absence of nutrient solutions can have a positive effect on the accumulation of nettle BCs.